A Conjoint Analysis of MBA Market Preferences When Choosing a University in Indonesia. Issue 1 (2nd January 2021) - Vincenthio, Audrie Gabriella; Renardi, Adama; Gunadi, Willy
Abstract: As the master's education market continues to expand, Indonesia will be amongst the key markets, especially for the MBA program. Universities are faced with challenges and opportunities in acquiring the increasing MBA market. The present study uses conjoint analysis to explore Indonesia's MBA market preferences in choosing a university by examining the tradeoffs made on attributes considered important in decision making, which has not previously been discussed. Therefore, the present study fills a gap in the research and aids practitioners in understanding the preferences of the MBA market in Indonesia, thus enabling them to design a program and marketing strategy accordingly. The results show that total tuition fees and lecturing time are the most critical attributes. Thus, attributes defining quality were found not to be of significant concern, while programs that offer alternatives in reducing financial burden and time were more valued.